Decoding the Red Genes in Bashu: Research on the Sichuan Mechanism and Path for Cultivating College Students' Sense of the Chinese National Community - Liu, Feiyang (Education Insights, 2026)
This paper systematically studies the value, mechanism, and practical path of Sichuan red culture in cultivating college students' sense of the Chinese national community, with the core goal of forging a strong sense of the Chinese national community, and leverages the unique resource endowment of Sichuan red culture. The study finds that Sichuan red culture has a high degree of internal consistency with the sense of the Chinese national community, and can effectively cultivate college students' sense of the community through four coordinated mechanisms: value guidance, emotional resonance, practical experience and innovative communication. At present, the cultivation work is faced with practical difficulties such as the impact of multiculturalism, insufficient development of red resources, inadequate educational integration and single communication methods. To this end, combined with the direction of in-depth research, this paper puts forward optimization strategies from four dimensions: top-level design, resource transformation, educational model and communication method, and clarifies the key directions for subsequent research, so as to provide theoretical support and practical reference for colleges and universities to use local red culture to cultivate college students' sense of the Chinese national community.